1993
DOI: 10.3109/10611869308996069
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Free and Non-Ionic Vesicular Sodium Stibogluconate in the Dog

Abstract: The pharmacokinetics and tissue distribution of antimony after the administration of sodium stibogluconate in a free form or entrapped in vesicles prepared from non-ionic surfactant were studied in the dog. Animals were given either one or two intravenous bolus injection(s) equivalent to 45 mg Sb kg-1 as free drug or 0.625 or 0.685 mg Sb kg-1 as vesicular drug. Blood samples were taken at various times after dosing and antimony levels in various tissues were determined at 3 h, 48 h and 6 days after dosing. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 16 publications
4
17
0
1
Order By: Relevance
“…Even though sodium stibogluconate and meglumine antimoniate are different pentavalent antimony complexes, the fact that both drugs showed identical pharmacokinetics in humans (10) justifies the present comparison. In the bone marrow, antimony levels in the range of 2 µg/g were found 3 and 48 h after administration (8). Strikingly, these levels are in the same range as those found in the present study.…”
Section: Da Schettini Et Alsupporting
confidence: 90%
See 3 more Smart Citations
“…Even though sodium stibogluconate and meglumine antimoniate are different pentavalent antimony complexes, the fact that both drugs showed identical pharmacokinetics in humans (10) justifies the present comparison. In the bone marrow, antimony levels in the range of 2 µg/g were found 3 and 48 h after administration (8). Strikingly, these levels are in the same range as those found in the present study.…”
Section: Da Schettini Et Alsupporting
confidence: 90%
“…Our results can also be compared to those obtained following a single iv injection in healthy dogs of another vesicular system given at 0.65 mg Sb/kg body weight (8). In the latter study, antimony levels of 5-30 µg Sb/g and 1-8 µg Sb/g were found in the bone marrow 3 and 48 h after administration, respectively.…”
Section: Da Schettini Et Almentioning
confidence: 56%
See 2 more Smart Citations
“…The greater efficacy of SSG-NIV in vivo presumably reflects its ability to modify its in vivo distribution and thus direct a great proportion of the drug dose to tissues (7,8). For example, tissue antimony levels (spleen, liver, femur, and humerus) at 6 days posttreatment were similar in free-SSG-and SSG-NIV-treated animals, despite a 70-fold difference in the drug dose administered (8). There was interstrain variability in susceptibility to SSG-NIV.…”
Section: Discussionmentioning
confidence: 99%